The Influence of Green Finance on Corporate Financial Performance in Indonesia with Environmental, Social, And Governance (ESG) As Moderating Variables - Ifah Masrifah (Jurnal Teknologi dan Manajemen Industri Terapan, 2022)
This study aims to analyze the influence of green finance on companies' financial performance in Indonesia, considering the moderating role of Environmental, Social, and Governance (ESG) disclosure. Amid the increasing urgency of climate change, the financial sector in Indonesia is shifting towards sustainable financing. Using signaling theory and stakeholder theory, this study evaluates whether green financial instruments, such as green bonds and green credit, improve corporate profitability (ROA and ROE). Data were taken from companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2025 period. The results show that green finance has a significant positive influence on financial performance, and this effect is stronger for companies with high ESG scores. This indicates that investors tend to assign a lower risk premium to companies that are transparent in their sustainability practices. These findings provide implications for regulators to strengthen the green taxonomy in Indonesia.